2014
DOI: 10.4103/0975-5950.154840
|View full text |Cite
|
Sign up to set email alerts
|

Double mandibular osteotomy with segmental mandibular swing approach to parapharyngeal space

Abstract: Surgical removal of benign tumors of the Parapharyngeal space (PPS) is the treatment of choice. PPS tumors may remain undetected for long periods of time and large tumors in the PPS can extend into the Retropharyngeal Space or into the Infra-Temporal Fossa. Anatomically, the mandible represents a significant obstacle to successful PPS surgery. Except for very small tumors, it is difficult to remove larger tumors from this region without some form of mandibular retraction. The standard mandibular “swing” approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…29 Lateral mandibulotomy (parasymphysis or ramus osteotomy) is an alternative osteotomy technique, which rather requires manipulation of the lateral structures, that is, facial nerve and parotid gland to access the entire PPS. A double mandibular osteotomy without lip splitting technique was described in 2007 by Kolokythas et al 30 and in 2014 by Satpathy et al 31 Both studies reported minimal complications and adequate exposure of the PPS including the skull base and pterygomaxillary fossa, as well as visualization of the great vessels. Some prefer the traditional transoral approach to manage select lesions in the prestyloid space.…”
Section: Discussionmentioning
confidence: 99%
“…29 Lateral mandibulotomy (parasymphysis or ramus osteotomy) is an alternative osteotomy technique, which rather requires manipulation of the lateral structures, that is, facial nerve and parotid gland to access the entire PPS. A double mandibular osteotomy without lip splitting technique was described in 2007 by Kolokythas et al 30 and in 2014 by Satpathy et al 31 Both studies reported minimal complications and adequate exposure of the PPS including the skull base and pterygomaxillary fossa, as well as visualization of the great vessels. Some prefer the traditional transoral approach to manage select lesions in the prestyloid space.…”
Section: Discussionmentioning
confidence: 99%
“…The upper cheek flap approach is optimal for the resection of larger tumors of the hard palate and the upper alveolus, particularly if located posteriorly. The mandibulotomy approach usually involves a lip-split, and has been preferred for advanced oral cancer because it can provide excellent exposure to the oral cavity and the oropharynx [17,18]. Compared to midline mandibulotomy, a paramedian mandibulotomy has merits for swallowing function since it preserves the geniohyoid and genioglossus muscles, and the anterior belly of the digastric muscle [19].…”
Section: Surgical Approachmentioning
confidence: 99%
“…Surgical access frequently requires manipulation of the mandible. Although mandibulotomy accompanied by lip splitting provides wide exposure of the oral cavity [ 45 , 46 ], this method was associated with many complication related to wound healing, fistulas, and bony union issues [ 47 , 48 ]. The introduction of alternative mandible-preserving techniques, including mandibular sparing, mandibular lingual release, and transcervical, transpharyngeal, and transhyoid approaches, all of which preserve mandibular integrity, has made it possible to avoid these complications [ 47 , 49 , 50 ].…”
Section: Technical Aspects Related To Tongue Reconstructionmentioning
confidence: 99%